Security in health-care information systems—current trends - Smith, E; Eloff, J.H.P (International journal of medical informatics (Shannon, Ireland), 1999)
Ever since health-care information systems have been implemented, their security is being considered an important issue, especially in the light of the fact that their data are deemed to comprise extremely sensitive information. The prospect of storing health information in electronic form raises concerns about patient privacy and data security. Any attempt to introduce computerised health-care information systems should, therefore, guarantee adequate protection of the confidentiality and integrity of patient information. At the same time, the patient information also needs to be readily available to all authorised health-care providers, in order to ensure the proper treatment of the patient. The principal aim of the present paper is, however, not to make a new contribution to the subject of security per se, but rather to give an overview of current trends in the security aspects of health-care information systems. The final section of the paper will be devoted to a number of proposals for further research possibilities in the domain of health-care information systems security.